Inhibition of α-amylase in vitro and in vivo hypoglycemic effect of methanol extract of Alchemilla viridiflora Rothm. - Radović Selgrad, Jelena; Ušjak, Dušan; Milenković, Marina; Kundaković-Vasović, Tatjana (Archives of Pharmacy, 2022)
Dry methanol extract (DER 3.95:1) of aerial flowering parts of Alchemilla viridiflora Rothm., Rosaceae, obtained after successive extraction with cyclohexane and dichloromethane, predominantly contains polyphenols, tannins (3.74%), mostly ellagic, and flavonoids (0.30%), hexosides of quercetin and kaempferol. It shows ACE inhibitory and anti-Helicobacter pylori activity in vitro. Based on the traditional use of the common A. vulgaris in the treatment of diabetes, the effect of this A. viridiflora extract on α-amylase activity in vitro and lowering blood glucose in rats were investigated. α-Amylase inhibitory activity was assessed using the 3,5-dinitrosalicylic acid method. Extract in doses of 50, 100 and 200 mg/kg, p.o., was administered to streptozotocin-induced diabetic rats for 20 days, and blood glucose level and weight of rats were monitored during treatment. Extract inhibited α-amylase activity at IC50 5.47 ± 0.30 mg/mL. A dose of 200 mg/kg significantly decreased blood glucose level after 10 (32.2%) and 20 days of treatment (38.3%). The effect of this dose was similar to the effect of the reference drug, glibenclamide. A dose of 100 mg/kg significantly increased glucose level by day 10 (50.5%) and a reduction in blood sugar level of 51.2% was observed only after 10 days. Body weight was correlated with changes in blood sugar levels. A dose of 50 mg/kg had no statistically significant effect. Results indicate a significant potential of A. viridiflora aerial parts in the treatment of diabetes, which must be confirmed by additional studies, and active ingredients need to be identified.